ASSISTANCE IN THE REVIEW OF PUBLIC SERVICE POLICIES AT PDAM DENPASAR BALI - Dewi, Ida Ayu Putu Kartini; Putri, Putu Indah Dianti; Wiraatmaja, I Putu Prana (LPPM Univ. Ibn Khaldun Bogor, 2023)
Public services are all activities in the context of fulfilling basic needs in accordance with the basic rights of every citizen and resident of an item, service and or administrative service provided by service providers related to the public interest. The problem to be discussed is the implementation of public service policies by the Regional Public Company for Drinking Water Tirta Sewakadarma for the people of Denpasar City. The technique used by the author is Purvosive Sampling, namely Snowball Sampling in determining the informants of this study, where in the in-sample technique, the number starts from a small number and then enlarges according to information needs. For the Denpasar City Government, considering that clean water services are a basic human need, through PDAM Tirta Sewakadarma it is hoped that the participation of local governments in providing these services is because water is a basic need for humans, of course, people need these types of products. the ability of PDAM Tirta Sewakadarma Denpasar City which has provided facilities to support employee work and provide a sense of comfort to customers, neat appearance, to payment points that provide convenience to customer.